Lycium barbarum polysaccharide protects against ethanol‐induced spermiotoxicity and testicular degeneration in Immp2l+/− mice. (6th March 2020) - Liu, Chunlian; Gu, Jiwei; Ma, Wenqian; Zhang, Qian; Song, Mengling; Ha, Lingxia; Xu, Xian; Jiao, Haiyan; Huo, Zhenghao
Abstract: Studies have indicated that high levels of ethanol exposure impaired spermatogenesis in mice. However, the effects of chronic and low‐dose alcohol consumption on susceptible populations remain unclear. The previous studies have confirmed that Immp2l mutant mice (Immp2l Tg(Tyr)979Ove or Immp2l −/− ) suffered from increased levels of oxidative stress(OS) and male infertility, heterozygous lmmp2l mice (Immp2l +/− ) showed no altered ROS levels under physiological condition. Lycium barbarum polysaccharide (LBP) significantly scavenge oxygen free radicals and enhance antioxidant enzyme activity. The objectives of present study were to research the effects of chronic and low‐dose alcohol‐induced damage on Immp2l +/−, explore the protective function of LBP and possible mechanism. The results indicated that chronic ethanol exposure leads to spermatogenic impairment and triggered a toxic effect on germ cell, 10 mg/kg LBP administration improved the quality of spermatozoon, decreased the ratio of apoptotic germ cells and the expression of Col1a1 and Col1a2, while increased the level of TNP2 and RPL31. In conclusion, the study may provide basic knowledge about LBP's important role against ethanol‐induced spermiotoxicity and testicular degeneration in Immp2l +/− mice, and the mechanism may be that LBP influenced the state of the spermatogenic epithelium by decreasing the expression of Collagen level leading to alterations in protein biosynthesis during the process of spermatogenesis.